Ecnomic Loáes Aáociated with Zabrotes subfaciatus (Boheman)(Coleoptera: bruchidae) and Acanthoscelides (Say)(Coleoptera: Bruchidae) Infestations of Stored dry Red Beans (Phaseolus vulgaris L.) in Southeastern Honduras - Espinal, R.=700 1 Higgins, R.; Wright, V.
(En, Es)
ilus., 23 ref.
Keywords: PHASEOLUS VULGARIS; PLAGAS DE PRODUCTOS ALMACENADOS; PERDIDAS POSTCOSECHA; PERDIDAS; PERDIDAS DE PESO; ZABROTES SUBFACIATUS; ACANTHOCELIDES OBTECTUS; COLEOPTERA; INSECTA; HONDURAS